The Effectiveness Based on Mindfulness Cognitive Therapy on Internalized Shame, Marital Disaffection and Tendency to Divorce in Unfaithful Couples - Azarmajd, Sadaf; KhoshLahjeh Sedgh, Anis (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to investigate the effectiveness of mindfulness-based cognitive therapy on internalized shame, marital disaffection, and inclination toward divorce in couples who had experienced infidelity. Methods: This research was conducted using a quasi-experimental design with pre-test and post-test and a control group. The statistical population of this study consisted of all couples who, due to experiencing infidelity by their spouses, referred to licensed counseling and psychotherapy centers of the Iranian Psychological and Counseling Organization, the State Welfare Organization, or psychiatrists licensed by the Iranian Medical Council (Anis Andisheh Clinic) in District 3 of Tehran, during the first quarter of 2024. In this study, the sample size for each of the experimental groups and the control group was 16 people (8 women and 8 men), and a total of 32 individuals were selected. According to the quasi-experimental design, they were chosen through convenience sampling from among volunteers and then randomly assigned to the experimental and control groups by lottery. Data collection instruments included the Internalized Shame Scale by Cook (1993), the Marital Disaffection Scale by Kaiser (1993), and the Inclination Toward Divorce Scale by Rusbult et al. (1986). In this study, mindfulness-based cognitive therapy consisted of eight weeks of two-hour sessions based on the mindfulness-based cognitive therapy protocol by Crane. Findings: The results of data analysis indicated that mindfulness-based cognitive therapy had an effect on internalized shame, marital disaffection, and inclination toward divorce in couples who had experienced infidelity. Conclusion: Considering the results, it can be stated that mindfulness-based cognitive therapy influences the research variables. It is suggested that further studies be conducted in this area to enhance external validity.